2010
DOI: 10.3390/m695
|View full text |Cite
|
Sign up to set email alerts
|

2-Methyl-3-{4-[2-(1H-tetrazol-5-yl)ethylamino]phenyl}-3H-quinazolin-4-one

Abstract: This present work aims at synthesizing a novel tetrazole from quinazolinone. 3-(4-Aminophenyl)-2-methyl-3H-quinazolin-4-one is converted into a nitrile by reacting it with acrylonitrile and triton B. The nitrile on treatment with NaN3, NH4Cl and DMF yielded the corresponding tetrazole. The tetrazole obtained was characterized by IR, 1H NMR, EI-MS and elemental analysis. The compound was screened for antimicrobial activity against Staphylococcus aureus, Escherichia coli, Candida albicans and Aspergillus niger.T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…A novel series of tetrazole compounds were reported to possess antimicrobial activity in vitro by the disc diffusion method measuring zones of inhibition. The results of the study showed that the synthesized compound 2-methyl-3-{4-[2-(1 H -tetrazol-5-yl-ethylamino]phenyl}-3 H -quinazolin-4-one ( 24 ) displayed fairly good antimicrobial activity against the test organisms, although the activity was less than that of the reference drugs (ciprofloxacin and fluconazole, respectively) [ 41 ]. It was reported that a series of new 5-thio-substituted tetrazole derivatives were synthesized and antimicrobial screening showed that all the synthesized compounds showed moderate activity against the tested organisms.…”
Section: Biological Activity Of Tetrazolium Derivativesmentioning
confidence: 99%
“…A novel series of tetrazole compounds were reported to possess antimicrobial activity in vitro by the disc diffusion method measuring zones of inhibition. The results of the study showed that the synthesized compound 2-methyl-3-{4-[2-(1 H -tetrazol-5-yl-ethylamino]phenyl}-3 H -quinazolin-4-one ( 24 ) displayed fairly good antimicrobial activity against the test organisms, although the activity was less than that of the reference drugs (ciprofloxacin and fluconazole, respectively) [ 41 ]. It was reported that a series of new 5-thio-substituted tetrazole derivatives were synthesized and antimicrobial screening showed that all the synthesized compounds showed moderate activity against the tested organisms.…”
Section: Biological Activity Of Tetrazolium Derivativesmentioning
confidence: 99%
“…Compounds 3-(4-(2-methyl-4-oxoquinazolin-3(4H)-yl)phenylamino)propanenitrile (1), 3,3'-(4,4'-sulfonylbis(4,1-phenylene)bis(azanediyl))dipropanenitrile (6), 3,3'-(6-phenyl--1,3,5-triazine-2,4-diyl)bis(azanediyl)dipropanenitrile (12) and 3,3,3',1,3,5-triazine-2,4,6--triyl)tris(azanediyl)tripropanenitrile (18) were prepared from primary amine by treatment with acrylonitrile and Triton B following reported literature (9).…”
Section: Methodsmentioning
confidence: 99%
“…Heterocyclic compounds have a great deal of attention because of their biological activity and also they make possible development of novel material with unique properties (Mostafa, 2010;Arulmurugan and Kavitha, 2010;Srinivas and Kumar, 2010;Caiazzo et al, 2004). One very interesting and promising class of heterocyclic is the series of 2,5-disubstituted-1,3,4oxadiazoles that have been proven to be effective antimicrobial, anti-inflammatory, fungicidal and bactericidal agents (Sharma et al, 2010;Narasimhan et al,2010;Banday et al, 2010;Dewangan et al, 2010;Bari et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%